Liquid Chromatographic Method for the Determination of Metformin and Nateglinide in Pharmaceutical Formulations - Lakshmi, K.S.; Rajesh, T.; Sharma, Shrinivas (Asian Journal of Chemistry, 2010)
A simple and sensitive reverse phase high performance liquid chromatographic method for the determination of metformin and nateglinide was developed on a Shimadzu class vp series HPLC system on a reverse phase Gemini C18 column (150 mm × 4.6 mm, i.d., 5 μ) using a mobile phase mixture containing methanol and phosphate buffer (pH 3) in the ratio of 60:40. The flow rate was 0.8 mL/min and effluents were monitored at 235 nm and eluted at 2.63 (metformin) and 4.51 min (nateglinide). Calibration curve was plotted with a range from 0.5-50.0 μg/mL for metformin and 0.06-6.00 μg/mL for nateglinide. The assay was validated for the parameters like accuracy, precision, robustness, detection and quantification limits and system suitability parameters. The method was applied for the assay of dosage forms. The results were found to be satisfactory and the method can be adapted for the routine quality control of the drugs in pure and pharmaceutical dosage forms.